ANALISIS PENGARUH INDIKATOR MAKROEKONOMI TERHADAP IMPOR BARANG INTRA-ASEAN - Lasma Melinda Siahaan (Quantitative Economics Journal, 2018)
This research aims to determine the factors that affect the amount of imported goods intra-ASEAN. Factors influencing the import of goods in this study are Gross Domestic Product (GDP), Inflation and Exchange Rate in each member country of ASEAN. The method used in this research is panel regression through Panel Least Square (PLS) by using program Eviews 10. The data used is panel data, consisting of ten ASEAN member countries and ten years of research from 2006 to 2015. The results of the analysis data show that GDP and inflation have a positive and significant effect on the imported goods intra-ASEAN, while the exchange rate has a negative and significant effect on the imported goods intra-ASEAN. Simultaneously, GDP, inflation and exchange rate have a positive and significant effect on imported goods intra-ASEAN.